Urban Religion in Late Antiquity - Asuman, Lätzer-Lasar; Clifford, Ando; Dirk, Steuernagel; Emiliano, Rubens Urciuoli; Hartmut, Leppin; Heidi, Wendt; Jörg, Rüpke; Lara, Weiss; Lätzer-Lasar, Asuman; Michael, Blömer; Michele Renee, Salzman; Paroma, Chatterjee; et al. (2020)
Urban Religion is an emerging research field cutting across various social science disciplines, all of them dealing with "lived religion" in contemporary and (mainly) global cities. It describes the reciprocal formation and mutual influence of religion and urbanity in both their material and ideational dimensions. However, this approach, if duly historicized, can be also fruitfully applied to antiquity. Aim of the volume is the analysis of the entanglement of religious communication and city life during an arc of time that is characterised by dramatic and even contradicting developments. Bringing together textual analyses and archaelogical case studies in a comparative perspective, the volume zooms in on the historical context of the advanced imperial and late antique Mediterranean space (2nd-8th centuries CE).